2015
DOI: 10.7150/jca.10705
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Tumor Size Assessment by Contrast-Enhanced Spectral Mammography and the Benefit of Additional Breast MRI

Abstract: Background - Contrast-enhanced spectral mammography (CESM) is a promising new breast imaging modality that is superior to conventional mammography for breast cancer detection. We aimed to evaluate correlation and agreement of tumor size measurements using CESM. As additional analysis, we evaluated whether measurements using an additional breast MRI exam would yield more accurate results.Methods - Between January 1st 2013 and April 1st 2014, 87 consecutive breast cancer cases that underwent CESM were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 19 publications
8
62
1
Order By: Relevance
“…The BI-RADS lexicon provides descriptors and assessment categories that can be used to predict the likelihood of malignancy for contrast-enhancing lesions on CE-MRI [18,19]. Recent studies have used MRI imaging characteristics for the evaluation of CEDEM images [9,10,13,14]; however, there is no data on the direct applicability of the MRI BI-RADS descriptors for contrastenhancing lesions on CEDEM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BI-RADS lexicon provides descriptors and assessment categories that can be used to predict the likelihood of malignancy for contrast-enhancing lesions on CE-MRI [18,19]. Recent studies have used MRI imaging characteristics for the evaluation of CEDEM images [9,10,13,14]; however, there is no data on the direct applicability of the MRI BI-RADS descriptors for contrastenhancing lesions on CEDEM.…”
Section: Introductionmentioning
confidence: 99%
“…When added to mammography, it has the potential to increase diagnostic accuracy [10,11] and can facilitate the visualization of breast lesions [11,12]. Accuracy, sensitivity, specificity, lesion detection rate, and assessment of tumor size are comparable to CE-MRI of the breast [13][14][15][16][17]. The BI-RADS lexicon provides descriptors and assessment categories that can be used to predict the likelihood of malignancy for contrast-enhancing lesions on CE-MRI [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…CESM provides images which are more familiar to surgeons with the same breast proportions as FFDM. The last but not the least is frugal consideration as CESM provides the same range of information for the fraction of breast MRI cost [12][13][14].…”
Section: Dromain Et Al Confirmed That the Initial Clinical Results Showmentioning
confidence: 99%
“…In addition, the fact that CESM requires approximately a 1.5 times greater radiation dose than conventional mammography (8, 11) has been seen as a disadvantage. However, to date, the false negative and false positive rates of CESM have been reported to be very low (11), and recent studies have demonstrated that it could have a sensitivity and sensibility similar to that of MRI, while having the advantage of being faster, much more economical, and not presenting the aforementioned contraindications of MRI (4, 6, 7). As such, CESM is a very promising imaging diagnostic tool, which may be useful in the diagnosis of complex breast lesions, as illustrated by this presented case report.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, contrast-enhanced breast magnetic resonance imaging (MRI) currently appears as the most sensitive technique to detect and stage breast cancer (4, 5). However, several recent studies have shown that the emerging dual-energy, contrast-enhanced digital mammography (CESM) method enables accurate detection of malignant breast lesions with a similar performance to that of MRI (4, 6-8), making it a good alternative to this expensive technique.…”
Section: Introductionmentioning
confidence: 99%